What makes a circuit likeable and how different input devices can influence the perception of tracks in racing games - Riccardo Galdieri (Elsevier, 2021)
Despite its significant role in the history of videogames, the world of racing games is still fairly unexplored. In this paper, we present the result of a study aimed at understanding how different hardware peripherals such as controllers and racing wheels can influence the perception of racing games, and how tracks’ features correlate with players’ liking of a given track based on the peripheral in use. A survey has been conducted on players who currently own a copy of F1, 2020, asking them to evaluate how much they like to hotlap and race on each circuit featured in the game, and what device they generally use to play. These results have been matched against objective classifications of racing tracks to find correlations between players’ preferences, the device in use, and circuits’ features. Different sets of variables have been analyzed, including physical features such as corners, height variation and length, racing features like average speed, gear shifts per lap and fastest lap, and non-racing features such as the number of real F1 races held on that track. Results show that players do prefer fast circuits with a lower number of gear shifts and corners regardless of their length, but they also indicate that this is more prominent on historical circuits, supporting the idea of potentially influencing external factors. Results also show that little difference is produced by using devices with different levels of natural mapping.